Thermodynamics of the Quark Gluon Plasma in the Early Universe - AL-ZAKI, Hamid (International Journal of Computational and Experimental Science and Engineering, 2020)
The recent progress in collider experiments provides us with valuable information to understand the properties of the quark-gluon plasma. In this study, we provide the analytical solution to the deferential equation of the time evolution of the temperature in the early Universe in the MIT bag model for gluons only. We discuss the equation of state of a QGP in a particular model, the possible signs for a plasma created in heavy-ion collisions and provide analytic solutions describing the time evolution of the energy density, temperature and pressure of this plasma in the early universe.